Development and Application of Machine Vision Recognition Technology in the Field of Mechanical Transmission - Luji Wu; Jiayin Qin; Anhu Li; Linjie Yang (Jixie chuandong)
An image acquisition method based on machine vision and its application in many fields are expounded； an image processing technology is introduced，and a schematic diagram of the processing results of each method is given by taking the gear tooth surface as an example； the characteristics of various classification and recognition technologies are summarized； finally，the application and development trend of machine vision recognition technology in the field of mechanical transmission，such as gear tooth surface damage recognition direction，are prospected.